2009
DOI: 10.1159/000205582
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enzymatically Modified Isoquercitrin, a Flavonoid, on Symptoms of Japanese Cedar Pollinosis: A Randomized Double-Blind Placebo-Controlled Trial

Abstract: Background: Flavonoids exert antiallergic and antioxidant effects. We investigated the efficacy of enzymatically modified isoquercitrin (EMIQ), a flavonoid, to relieve symptoms of pollinosis. Methods: In a parallel-group, double-blind placebo-controlled study design, 20 subjects with Japanese cedar pollinosis took two capsules daily of 100 mg EMIQ or a placebo for 8 weeks during the pollen season. Subjective symptoms and activities of daily living (ADL) scores were recorded every day, and the quality of life (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…Remberg et al . 20 have reported that significant nasal and ocular symptom relief was observed in allergic rhinitis patients with topical nasal application of Artemisia abrotanum L. extract, which contains flavonols such as centauredin, casticin and quercetin. Thus, we also thought that topical application of onion extracts might have effects for control of allergic rhinitis symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Remberg et al . 20 have reported that significant nasal and ocular symptom relief was observed in allergic rhinitis patients with topical nasal application of Artemisia abrotanum L. extract, which contains flavonols such as centauredin, casticin and quercetin. Thus, we also thought that topical application of onion extracts might have effects for control of allergic rhinitis symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the results of recent clinical trials using flavonoid extracts or flavonoids indicate that flavonoids have beneficial effects on allergic rhinitis [104,105,106,107,108,109,110,111,112]. …”
Section: Human Intervention Studies Of Flavonoids In Asthmamentioning
confidence: 99%
“…141 With respect to quercetin, the approved food additive enzymatically-modified isoquercitrin (EMIQ), unlike quercetin, is highly soluble, but is metabolized to yield free quercetin at the intestinal brush border; a human pharmacokinetic study found that when equimolar amounts of quercetin and EMIQ were administered orally, the plasma levels of quercetin achieved were twenty-fold higher with EMIQ. [147][148][149][150][151] This agent apparently has not yet been tested in rodent tumor models.…”
Section: Flavones/flavonols As Natural Inhibitors Of Ck2mentioning
confidence: 99%